Influence of power loading on the aerobic readiness of judoists - Pashintsev, V.; Podlivaev, B.; Korjenevsky, A. (International Journal of Wrestling Science, 2011)
The use of speed-power orientation has increased the maximum ventilation (MVL) from 105 to 114 l / m, which also improves performance of external breathing. Thus, we can say that speed and power load increases the strength of respiratory muscles, maximum ventilation and improves bronchial patency lungs, which improves performance of external respiration and aerobic capacity develops judoka.